Unconventional oilseeds and oil sources - Mariod, Abdalbasit Adam; Mirghani, Mohamed Elwathig Saeed; Hussein, Ismail H. (Elsevier (Academic Press), 2017)
Unconventional Oilseeds and New Oil Sources: Chemistry and Analysis is presented in three parts, with each section dedicated to different types of oil sources. Part One deals with plants (vegetable, herbs, shrubs), such as Hibiscus, Mexican Poppy, Cucumber, Squashes, Sesame, etc. Part Two presents unconventional oils found in trees (like Balanites aegyptiaca, Annona squamosal and Catunaregam nilotica), and Part Three deals with new oils found in insects, as in the water melon bug and sorghum bug.